KEANEKARAGAMAN TUMBUHAN PAKU DI BUKIT BOTAK KABUPATEN MUSI RAWAS SUMATERA SELATAN - Ikna Pramudita; Merti Triyanti; Yunita Wardianti (Jurnal Biosilampari : Jurnal Biologi, 2021)
This study aimed to determine the types of Pteridophyta and to determine the index of diversity, dominance, and evenness in the Botak Hill. The research method used is descriptive quantitative. The data collection techniques in this study were exploratory methods and purposive sampling techniques. Based on the results of the study found as many as 1620 individual, consist of 24 species, 16 genera, 8 families and 4 orders. The results of the analysis of the diversity index of 2.851 (medium category), the dominance index value of 0.06 (low category), the evenness index of 0.679 (high category). There were 24 species of ferns found in Botak Hill, diversity was in the medium category, dominance was in the medium category and evenness was in the high category.